MANAJEMEN ZAKAT FITRAH PADA MASA COVID-19 DI KELURAHAN SIMANGAMBAT KECAMATAN SIABU MANDAILING NATAL - Jureid Jureid (Institut Agama Islam Negeri Metro, 2023)
The management of zakat fitrah during the Covid-19 era is something new. There is a shift from manual to digital patterns. This research wants to see how the management of zakat fitrah in the Simangambat Village, Siabu District during the Covid-19 period. The method that used in this research is descriptive qualitative method, namely by describing the management patterns carried out by zakat managers in the Village. There is a shift in the management pattern of zakat fitrah in Simangambat Village, Siabu sub-district, Mandailing Natal Regency. Before Covid-19 broke out, zakat was distributed manually door to door in the pre-Covid-19 era, namely directly distributed to Mustahik's house by Amil. Meanwhile, during the Covid-19 period, zakat was paid by transfer to an account (digitally) in the form of money for those who have accounts recorded in the Kelurahan Government database as zakat fitrah managers.